2004
DOI: 10.1016/j.orthres.2004.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Coating of titanium implants with type‐I collagen

Abstract: Purpose: Type-I collagen, the major structural protein in bone, has beneficial properties regarding bone regeneration. Little is known about the potential effects of collagen coating on orthopedic implants. method^ 3 to 6 @cm2 of lyophilized type-I collagen was absorbed on titanium rods. Six coated and uncoated pins of 0.9 mm diameter were inserted into the tibia of adult male Wistar rats for 1, 2, 4, 7, 14, and 28 days. Specimens were embedded in methacrylate-based Technovit 9100N resin. From one portion cutt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
86
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(92 citation statements)
references
References 46 publications
3
86
0
3
Order By: Relevance
“…If confirmed, these observations could open the way to finely-tuned BMTiS, where, depending on the specific site and application, a specific molecule or set of molecules could be used to its best effect. Rammelt et al (2004) presented a study in rat, involving coating by adsorption of type-I collagen on titanium rods. Coated and uncoated pins were inserted into the tibia of adult rats and histology and immunohistochemistry were performed at 1, 2, 4, 7, 14 and 28 days.…”
Section: Morramentioning
confidence: 99%
“…If confirmed, these observations could open the way to finely-tuned BMTiS, where, depending on the specific site and application, a specific molecule or set of molecules could be used to its best effect. Rammelt et al (2004) presented a study in rat, involving coating by adsorption of type-I collagen on titanium rods. Coated and uncoated pins were inserted into the tibia of adult rats and histology and immunohistochemistry were performed at 1, 2, 4, 7, 14 and 28 days.…”
Section: Morramentioning
confidence: 99%
“…Recent studies concerning collagen coatings on Ti hard-tissue implants have demonstrated their effective roles in stimulating cellular responses [11], increasing bone remodeling [12,13], and improving bone growth and bone-implant contact [14]. Therefore, hybrids of collagen and HA have greater potential for clinical applications than their pure HA or collagen equivalents, because they benefit from the advantageous properties of both materials, while retaining a similar composition and structure to that of human hard tissues.…”
Section: Introductionmentioning
confidence: 99%
“…47 Several ECM components, such as collagen, fibronectin, and GAGs, have shown the ability to control inflammatory responses. [48][49][50] The ECM scaffolds in our study maintained considerable amount of natural collagen I and fibronectin, which may exert immunomodulating effects in vivo. Different decellularization methods resulted in ECM scaffolds with different components and mechanical properties, which could be applied in different tissue regeneration applications.…”
mentioning
confidence: 99%